2008
DOI: 10.1592/phco.28.10.1223
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Oral Posaconazole in Neutropenic Patients Receiving Chemotherapy for Acute Myelogenous Leukemia or Myelodysplastic Syndrome

Abstract: Oral posaconazole 200 mg 3 times/day provided plasma concentrations adequate for preventing IFIs. No dosage adjustments are recommended based on any covariate tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
104
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 35 publications
12
104
3
Order By: Relevance
“…A steady-state target posaconazole plasma level of 500 ng/ml has previously been used in a trial of patients with compromised gastrointestinal function who were at high risk for IFD (19). The target in this study (C avg Ͼ500 ng/ml in Ͼ90% of subjects) was higher than previously seen with the oral suspension (25). The upper end of the target exposure range (C avg Յ2,500 ng/ml) was selected to be within the range at which posaconazole exposure response and safety have been characterized for most subjects in earlier clinical studies for the prophylaxis and treatment of refractory IFD.…”
Section: Discussionmentioning
confidence: 78%
“…A steady-state target posaconazole plasma level of 500 ng/ml has previously been used in a trial of patients with compromised gastrointestinal function who were at high risk for IFD (19). The target in this study (C avg Ͼ500 ng/ml in Ͼ90% of subjects) was higher than previously seen with the oral suspension (25). The upper end of the target exposure range (C avg Յ2,500 ng/ml) was selected to be within the range at which posaconazole exposure response and safety have been characterized for most subjects in earlier clinical studies for the prophylaxis and treatment of refractory IFD.…”
Section: Discussionmentioning
confidence: 78%
“…A pharmacokinetic subanalysis of a pivotal phase III posaconazole trial did not demonstrate an effect of H 2 antagonists on posaconazole concentration (18); however, a pharmacokinetic study by the manufacturer found a 39% reduction in posaconazole peak concentration (C max ) and total exposure (AUC) when cimetidine was coadministered with posaconazole (27). While this interaction is attributed to altered gastric pH caused by cimetidine reducing posaconazole absorption, the product information states that no posaconazole dosage adjustment is needed when coadministered with H 2 antagonists other than cimetidine, without provision of supporting evidence (27).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the coadministration of posaconazole with metoclopramide, a prokinetic agent, decreased the level of posaconazole absorption (i.e., it decreased the C max by 21% and the AUC by 19%). This decrease is not likely to be clinically relevant, given the wide therapeutic index of posaconazole (17,19). This association between increased gastric emptying and decreased posaconazole exposure is consistent with the findings of an analysis of the pharmacokinetics of posaconazole in allogeneic HSCT recipients with GVHD, in which patients with diarrhea had a lower C max than those without diarrhea (median C max s, 623 Ϯ 685 ng/ml [n ϭ 18] versus 1,460 Ϯ 972 ng/ml [n ϭ 223], respectively) (17).…”
Section: Vol 53 2009 Posaconazole Under Various Gastric Conditions 961mentioning
confidence: 99%
“…The pharmacokinetics of posaconazole have been studied in healthy volunteers (6), patients with refractory IFIs or febrile neutropenia (34), patients with acute myelogenous leukemia and neutropenia (19), and HSCT recipients with GVHD (17) or neutropenia with or without mucositis (13). Posaconazole is well absorbed after oral administration and has a large volume of distribution (V), suggesting extensive tissue distribution (6).…”
mentioning
confidence: 99%